The Theoritical Framework On Factors Affecting Consumer Impulsive Buying Behaviour In Retail Environment - Dr .M. Kishore Babu, Mr .K. Balaji , (International Journal of Scientific Research and Management (IJSRM), 2015)
In modern era, the increase in personal disposable incomes and easy to get credit availability have madeimpulsive purchasing in retail environment a major leisure and lifestyle activity. Impulsive purchasebehavior is driven by hedonistic or pleasure seeking goals causes a consumer to experience desires forproducts. The purpose of this article is to justify factors affecting consumer impulsive purchase behavior inretail environment after performing theoretical analysis of impulsive purchase models. This article shows thevarious frameworks for determining impulse buying behavior cues and reasons how the impulse buying willoccurs in individuals Research methodology used in the article is comparison analysis of scientific literatureand various case studies.